Conventional partial pancreatoduodenectomy versus an extended pancreatoduodenectomy (triangle operation) for pancreatic head cancers - study protocol for the randomised controlled TRIANGLE trial - Heger, Patrick; Hackert, Thilo; Diener, Markus K.; Feißt, Manuel; Klose, Christina; Dörr-Harim, Colette; Möhlenbrock, Friedhelm; Büchler, Markus W.; Mihaljevic, André Leopold (Trials, 2023)
Pancreatic ductal carcinoma (PDAC) is the fourth most frequent cause of cancer-related death in the Western world, and its incidence is rising. In patients that undergo curative resection, local recurrence (LR) is frequent. A recently described surgical technique of extended pancreatoduodenectomy (PD) termed the TRIANGLE operation has been proposed as a promising approach to reduce LR and improve disease-free survival in PDAC patients.